Esophageal perforation during laparoscopic sleeve gastrectomy: Complication of bougie insertion. (April 2021) - Tadayon, Seyed Mohammad Kazem; Moeinvaziri, Nader; Amini, Masoud; Setoodeh, Maryam; Haghighat, Neda
Highlights: Esophageal perforation is an uncommon complication may occur during bariatric surgery. The early diagnosis and the optimal therapeutic approach may reduce the mortality rate. The bougie transoral insertion should be done by an anesthesiologist to prevent unwanted complications such as perforation. Abstract: Introduction and importance: Esophageal perforation (EF) is an uncommon complication of bariatric procedures, mostly related to the intraoperative use of bougie that is used for gastric calibration. Case presentation: Here, we present a 33-year-old woman who underwent laparoscopy sleeve surgery (LSG). Due to perforation in the cervical site of the esophagus caused by bougie insertion, she developed subcutaneous emphysema on the first post-operative day. She immediately underwent reconstructive esophageal surgery under the probable diagnosis of having a cervical esophagus perforation. The patient's condition was stable in the postoperative period and discharged after 10 days. Clinical discussion: The patients who present symptoms including subcutaneous emphysema, cervical pain, dysphagia, dysphonia, and fever post-surgery have to be considered for probably EF. The early optimal diagnosis works up and therapeutic approach should be performed as soon as possible to prevent mortality. Conclusion: EP caused by a bougie insertion is an uncommon complication that is associated with high mortality rates if the diagnosis and treatment were delayed. The risk of using a bougie during surgery should not be underestimated and have to be inserted with extreme caution and careful guide of surgeon.